József Szikura Botanical Garden - Kohut Erzsebet; Sikura Anita; Kopor Zoltan; Kohut Erzsébet; Szikura Anita; Kopor Zoltán; Kolozsvári István; Когут Ержебет; Коложварі Степан; Копор Золтан; Сікура Аніта (T.H. Shevchenko National University «Chernihiv Colehium», 2024)
Abstract. Objective is to study and analyse the history of the creation of the József Szikura Botanical Garden, the results of its scientific, educational and environmental work. Materials and methods of the study. The collections of the natural flora plants established by Professor József Szikura in 2011 in the village of Velyki Berehy, located 8 km northeast of the city of Berehove, Zakarpattya region were studied. The main criteria for assessing the plants diversity in the botanical garden were the following: the qualitative and quantitative composition of the collections, their condition, the results of plant propagation, the possibility of repatriating them to natural ecosystems, the effects of research work, and educational activities. The plant compositions were analyzed, and the species composition of the plots was studied. The role of the botanical garden in preserving the gene pool of flora was also assessed by the qualitative and quantitative composition of the long-lived seed bank. The results of the cultivation and acclimatisation of species of the world flora and the Carpathians have been evaluated since 2012. The evaluation of the results, cultivation and acclimatization of species of the world flora and the Carpathians has been carried out since 2012. Scientific novelty. For the first time, the compositional and systematic composition of the József Szikura Botanical Garden was analysed in the context of successful solution of problems related to the conservation of plant diversity in artificially created phytocoenoses of Transcarpathia. Based on the results of the study, an electronic catalogue (EC) of the Bank of long-lived seeds was created for the first time. Conclusions. According to the results of the inventory analysis, it was determined that the area of 0,82 ha is represented by plants of different natural flora, the taxonomic composition of the collection of which includes 89 families, 468 species, 149 varieties and cultivars. The most numerous families in the collection are Amaryllidaceae J.St.-Hil., Iridaceae Juss., Poaceae Barnhart, Caryophyllaceae Juss., Lamiaceae Martinov, Asteraceae Giseke, Cupressaceae Gray. Three Allium L. species and two Iris L. species are listed in the Red Data Book of Ukraine. The collection contains plants listed in the IUCN Red List (Allium – 5 species, Iris – 2 species) and the relict Syringa josikaea J.Jacq. ex Rchb. The analysis of the composition of the Seed Bank showed the following distribution between taxa – 249 species belonging to 47 families. The József Szikura Botanical Garden effectively combines research work on the study and protection of biodiversity, introduction and acclimatisation, reproduction and efficient use of plants, and functioning as an educational regional centre for the dissemination of ecological and ethnographic knowledge, education and upbringing of the population in the traditions of caring for nature and preserving the cultural heritage of the region.

Резюме. Мета роботи. Прослідкувати та проаналізувати історію створення Ботанічного саду імені Йосипа Сікури, результати наукової, просвітницької та природоохоронної роботи. Матеріали та методи дослідження. Досліджувалися колекції рослин природної флори, закладені професором Йосипом Сікурою у 2011 році на території села Великі Береги, розташованому за 8 км на північний схід від міста Берегове Закарпатської області. Основними критеріями оцінки різноманітності рослин у ботанічному саду були такі: якісний і кількісний склад колекцій, їх стан, результати розмноження рослин, можливості репатріації їх у природні екосистеми, наслідки виконання науково-дослідних робіт, заходи освітньо-виховного характеру. Аналізувалися композиції рослин та видовий склад ділянок. Роль ботанічного саду для збереження генофонду рослинного світу оцінена також за якісним та кількісним складом банку насіння з довготривалим терміном зберігання. Проводилася оцінка результатів, культивування й акліматизації видів світової флори та Карпат з 2012 року. Наукова новизна. Вперше проаналізовано композиційний та систематичний склад ботанічного саду імені Йосипа Сікури у контексті успішного вирішення задач, пов’язаних зі збереженням різноманітності рослин у штучно створених фітоценозах Закарпаття. На основі результатів дослідження вперше сформовано електронний каталог (ЕК) Банку насіння з тривалим терміном зберігання. Висновки. За результатами інвентаризаційного аналізу визначено, що на площі 0,82 га представлено рослини різних природних флор, таксономічний склад колекції яких нараховує 89 родин, 468 видів, 149 сортів і культиварів. Найчисленнішими родинами в колекції є Amaryllidaceae J.St.-Hil., Iridaceae Juss., Poaceae Barnhart, Caryophyllaceae Juss., Lamiaceae Martinov, Asteraceae Giseke, Cupressaceae Gray. Три види Allium L. та два види Iris L. занесені до Червоної книги України. У колекції є рослини, занесені до Червоної книги МСОП (Allium – 5 видів, Iris – 2 види), та релікт Syringa josikaea J.Jacq. ex Rchb. Аналіз складу Банку насіння показав такий розподіл між таксонами – 249 видів, що належать до 47 родин. Ботанічний сад імені Йожефа Сікури ефективно поєднує науково-дослідну роботу з вивчення та охорони біорізноманіття, інтродукції та акліматизації, розмноження та ефективного використання рослин та функціонування як освітній регіональний центр поширення екологічних та етнографічних знань, освіти та виховання населення в традиціях дбайливого ставлення до природи та збереження культурної спадщини краю.
Ботанічний Сад імені Йосипа Сікури
Full Issue: https://journal.chnpu.edu.ua/index.php/biota/issue/view/17
Keywords: biodiversity conservation; introduction; collection of natural flora species; biotechnology; seed bank